Effects of solvent dols on the synthesis of ZnFe2O4 particles and their use as heterogeneous photo-fenton catalysts - Chiavone Filho, Osvaldo (2014)
A solvothermal method was used to prepare zinc ferrite spinel oxide (ZnFe2O4) using ethylene glycol and 1,4 butanediol as solvent diols, and the influence of diols on the physical properties of ZnFe2O4 particles was investigated. The produced particles were characterized by X-ray powder diffraction (XRD), atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR) and nitrogen adsorption isotherms, and the catalytic activity for the organic pollutant decomposition by heterogeneous photo-Fenton reaction was investigated. Both solvents produced particles with cubic spinel structure. Microporous and mesoporous structures were obtained when ethylene glycol and 1,4 butanediol were used as diols, respectively. A higher pore volume and surface area, as well as a higher catalytic activity for the pollutant degradation were found when 1,4 butanediol was used as solvent